Good teaching as a messy narrative of change within a policy ensemble of networks, superstructures and flows. Issue 1 (2nd January 2019) - Simmie, Geraldine Mooney; Moles, Joanne; O'Grady, Emmanuel
ABSTRACT: This paper examines 'good teaching' within a policy ensemble where teachers' subjectification and practices are underpinned by new modes of evaluation and enforcement. Although the paper is written with specific concern for teachers in the Republic of Ireland, the literature demonstrates that concerns raised resonate internationally. Theoretical frameworks are drawn from Bernstein's pedagogic device and 'rules of evaluation' (2000, p. 34) and the tyranny of number, networks and superstructures found in policy research. The study includes a limited analysis of the policy ensemble in 'Austerity Ireland' and contextual understandings and perspectives of a purposive sample of experienced teachers ( n = 54). Critical analysis generated three themes: multiple perspectives about 'good teaching', a strongly perceived pedagogy of oppression and low ethical trust in reported interactions at some schools and with the state inspectorate. Conclusions position 'good teaching' within the super-complexity of a messy narrative of change and flows enacted with a diversity of inquirers and institutions. The study questions the role of state inspectors as arbiters of 'good teaching' and challenges the academy of teacher education in assuring productive discursive gaps for education as a social responsibility for public-interest values.